Cancer cachexia-anorexia syndrome and skeletal muscle wasting - Jurdana, Mihaela (Radiology and oncology (Ljubljana), 2009)
Cachexia-anorexia syndrome is a common and important indicator of cancer. It occurs in 30% to 80% of cancer patients. Cachexia means "bad condition" and may be present in the early stages of tumor growth, before any signs of malignancy. Cancer cachexia is a syndrome of progressive body wasting, characterized by loss of adipose tissue and skeletal muscle mass. In most cancer patients, cachexia is characteriyed by anorexia, which implies a failure of food intake, regulated through a complex system of hormones and neuropeptides. A decline in food intake relative to energy expenditure is a fundamental physiologic derangement leading to cancer associated weight loss. The weight loss in patients with cachexia-anorexia syndrome differs from that in caloric starvation or anorexia nervosa. The pathophysiology of cancer cachexia is not fully understood; however, studies have shown that cytokines are important in the alteration of the carbohydrate, lipid and protein metabolism. Cancer, prolonged bed rest, HIV infection and aging are conditionsin which muscle wasting is a common feature. An intervention that may potentially attenuate the progression of muscle wasting in cancer patientsis resistance exercise training, defined as multiple repetitions of static or dynamic muscular contractions that increase muscle mass. The main components of the pathological state of cachexia are anorexia and metabolic abnormalities such as fat depletion and muscle protein catabolism. Future developments may concentrate on the molecular abnormalities of cachexia and on examination of the functional benefit of resistance exercise training for cancer related muscle wasting.
Keywords: anoreksija; kaheksija; rak (medicina); zapleti